Experiências territoriais o design estratégico e suas implicações em contextos urbanos - Machado, Taís Lagranha (Universidade do Vale do Rio dos Sinos, 2014)
The constant process of transformation of society points to new challenges to be faced in relation to urban contexts. Among these is the need for a new look to the city's public spaces. These need to be seen by a more human dimension in the sense that, in addition to important structures in shaping urban form and function, play a social role, as the territory of social representations, the construction of meanings and symbolic exchanges between individual and society. Added to this context, the influences of the new ways of life (characteristic of contemporaneity) that require new ways of designing and act on the territory. For both, the public address space for a human bias points to the need for understanding the relationships that occur in the range of persons related to everyday experiences. Thus, this research aims to explore the strategic design as a process to port a look from the user experience, to territorial issues. Different authors stress the potential of design to address complex strategic realities, from the use of interdisciplinary methodologies, tools and projective centered focus on people. To do so, rescues if the visions of authors who address the three main issues to be addressed: the design as a methodology, user experience and public space. From an exploratory research, we seek to understand how projetual approach to strategic design can contribute to improve the experiences of users in public spaces. The research covers a combination of instruments to collect information, including the use of collaborative cartography to understand how to give the relationship between the user and the public space. As a result of this study, if point-what are the experiences of users in the public space of a given territory, the elements that evoke these experiences and what paths to empower them, through opportunities to design. We highlight the methodological process to understand this context, as the main contribution of this study.
Keywords: Design estratégico; Experiência do usuário; Design aplicado ao território; Espaço publico; Cartografias; Strategic design; User experience; Design applied to the territory; Public space; Cartography; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial